Steady State Temperature Distribution Calculation in BN-350 Reactor Fuel Rod - Rashid, Jamal M. (Sulaimani Journal for Pure and Applied Sciences, 2002)
The steady state temperature distribution in one dimension for BN-350 reactor fuel rod has been calculated via solving heat conduction equation numerically. The calculations covers the case of constant and variable heat transfer coefficient considering different heat flux and inlet reactor core temperature. The obtained results at average heat flux and core inlet temperature have been compared with reported results, it is found that these results could be a good references for reactor designing and for reactor safety processes when compared with higher values of material melting points.
Keywords: Temperature distribution; BN350 reactor